2010
DOI: 10.1074/mcp.m900568-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Interactome Mapping of the Phosphatidylinositol 3-Kinase-Mammalian Target of Rapamycin Pathway Identifies Deformed Epidermal Autoregulatory Factor-1 as a New Glycogen Synthase Kinase-3 Interactor

Abstract: The phosphatidylinositol 3-kinase-mammalian target of rapamycin (PI3K-mTOR) pathway plays pivotal roles in cell survival, growth, and proliferation downstream of growth factors. Its perturbations are associated with cancer progression, type 2 diabetes, and neurological disorders. To better understand the mechanisms of action and regulation of this pathway, we initiated a large scale yeast two-hybrid screen for 33 components of the PI3K-mTOR pathway. Identification of 67 new interactions was followed by validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 101 publications
5
64
1
Order By: Relevance
“…Thus, the results from our initial siRNA experiments strongly suggest our DENV-human interactome is enriched in proteins relevant to DENV infection. Consistent with this conclusion, 57% of our interactions were confirmed in the split-luciferase assay, which is comparable to other high quality yeast two-hybrid studies (75)(76)(77).…”
Section: Fig 3 Enriched Annotation Terms and Pathways Among The Humsupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, the results from our initial siRNA experiments strongly suggest our DENV-human interactome is enriched in proteins relevant to DENV infection. Consistent with this conclusion, 57% of our interactions were confirmed in the split-luciferase assay, which is comparable to other high quality yeast two-hybrid studies (75)(76)(77).…”
Section: Fig 3 Enriched Annotation Terms and Pathways Among The Humsupporting
confidence: 76%
“…Thirteen pairs (57%) yielded a significant increase in luciferase activity relative to both empty vector controls (p value Ͻ 0.02); we consider this set to represent true positives in the split-luciferase assay. This rate of confirmation is similar to those observed for other high quality large-scale yeast two-hybrid screens, which range from 20 to 85% (22,(75)(76)(77).…”
Section: Mapping the Denv-human Protein Interactionsupporting
confidence: 72%
“…As a result, we found that 59 candidate genes have been connected to SCZ [34][35][36][37][38], 77 candidate genes have been linked to T2D [39][40][41][42][43], while 25 candidate genes [44][45][46][47][48][49] have been implicated to both SCZ and T2D with various studies (Additional file 5). Totally, 161 candidate genes (~45% of all candidate genes) have been related to either SCZ or T2D or both diseases with various experimental approaches, further proving the rationale of "function association" in the application of disease related gene inference.…”
Section: New Candidate Risk Gene Inferencementioning
confidence: 95%
“…To elucidate the mechanism of action of CKIP-1 in cell fusion, a yeast two hybrids screen was performed to identify new CKIP-1 interactors (Pilot-Storck et al, 2010). The Arp2/3 subunit ARPC1A was identified as a direct binding partner for CKIP-1 (Fig.…”
Section: Rna Interference-mediated Inhibition Of Ckip-1 Blocks Mammalmentioning
confidence: 99%
“…We examined muscle fibre formation in Ckip-1 antisense morpholino oligonucleotide injected zebrafish embryos and show that Ckip-1 knock down in zebrafish embryo impairs fast-twitch myoblast fusion. Search for CKIP-1 binding partners (Pilot-Storck et al, 2010) identified ARPC1A subunit of Arp2/3 actin nucleation complex. We demonstrate that CKIP-1 regulates cell morphology and lamellipodia formation through membrane recruitment of Arp2/3 complex.…”
Section: Introductionmentioning
confidence: 99%